Cross-linked polymer hydrogels with embedded semiconductor nanocrystals - Saiuk, Dmytro; Bukartyk, Natalya; Shevchuk, Oleh; Tokarev, Viktor (Видавництво Львівської політехніки, 2017)
Cross-linked hydrogels containing metal cations were synthesized via radical copolymerization of hydrophilic monomers and nanocomposite hydrogels were obtained on their basis using in situ sol-gel synthesis of semiconductor nanocrystals directly in hydrogel matrices. The influence of metal ions onto copolymerization kinetics and hydrogel crosslinking degree was studied. It was shown that nanocrystal size depends to a large extent on the density of hydrogel network.
Keywords: cross-linked hydrogels; copolymers; radical copolymerization; nanocomposites; semiconductor nanocrystals